2012
DOI: 10.1117/1.jbo.17.6.061210
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the cerebral hemodynamic response function in single blood vessels by functional photoacoustic microscopy

Abstract: Abstract. The specificity of the hemodynamic response function (HRF) is determined spatially by the vascular architecture and temporally by the evolution of hemodynamic changes. Here, we used functional photoacoustic microscopy (fPAM) to investigate single cerebral blood vessels of rats after left forepaw stimulation. In this system, we analyzed the spatiotemporal evolution of the HRFs of the total hemoglobin concentration (HbT), cerebral blood volume (CBV), and hemoglobin oxygen saturation (SO 2 ). Changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 42 publications
0
26
0
1
Order By: Relevance
“…For instance, PA imaging technology is especially suitable for evaluating the progressive changes in the penumbra area of focal ischemia because of its attributes such as the deeper tissue penetration depth and intrinsic blood contrast. Recently, our studies have shown that functional photoacoustic microscopy (fPAM) can be used for the contrast agent-free imaging of functional CBV and hemoglobin oxygen saturation (SO 2 ) changes in the rat cortex following peripheral sensory stimulation (Hu et al, 2009;Liao et al, 2012a;Liao et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, PA imaging technology is especially suitable for evaluating the progressive changes in the penumbra area of focal ischemia because of its attributes such as the deeper tissue penetration depth and intrinsic blood contrast. Recently, our studies have shown that functional photoacoustic microscopy (fPAM) can be used for the contrast agent-free imaging of functional CBV and hemoglobin oxygen saturation (SO 2 ) changes in the rat cortex following peripheral sensory stimulation (Hu et al, 2009;Liao et al, 2012a;Liao et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…This ECoG-fPAM system allows the simultaneous assessment of two important variables in the pathophysiology of stroke, i.e., changes in regional cerebral perfusion (CBV and SO 2 ) 22 and neuronal integrity (SSEP, coherence, and ADR). 27 In this PTI stroke rat model, a focal infarct was created in the right hemisphere S1FL region by targeting a distal branch of the MCA.…”
Section: Advantages Of Ecog-fpam Setup For the Study Of Strokementioning
confidence: 99%
“…The vessel pixel was defined as the pixel that possessed a PA signal that was three times greater than the background signal. 21,22,35 Functional images of SO 2 changes ½ΔI Fð560Þ ðtÞ at a given time point t in each block were assessed according to the following equation: …”
Section: Data Analysis Of Measured Cbv and Somentioning
confidence: 99%
See 2 more Smart Citations